Islamic Legal Review of Online Lending Practices (A Case Study of the Community in Muara Sabak Timur District) - Saputra, Syari Muda; Wargo; Fatimah, Siti; Masvood (CV. Zabags Qu Publish, 2026)
The rapid expansion of online lending services in Indonesia has increased public access to financing while simultaneously raising legal, ethical, and Sharia compliance concerns. This study aims to examine online lending practices in Muara Sabak Timur District and assess their conformity with Islamic legal principles. Employing a qualitative case study design, the research draws on in-depth interviews, field observations, and document analysis involving users of online lending services. The data were analyzed thematically to identify patterns of practice, underlying driving factors, and their social as well as normative implications. The findings indicate that the use of online loans is predominantly driven by consumptive needs and facilitated by ease of access and rapid disbursement, whereas users’ understanding of cost structures and contractual (akad) arrangements remains limited. The imposition of interest, ambiguity in contractual terms, and certain debt collection methods suggest potential inconsistencies with the principles of riba, gharar, and justice in muamalah. This study contributes to strengthening Islamic economic law analysis within the context of digital finance and provides a foundation for developing more equitable and Sharia-compliant digital financing models.